PERUBAHAN ANATOMI DAN KANDUNGAN OLIGOSAKARIDA PADA BENIH REKALSITRAN Avicennia marina AKIBAT PERBEDAAN LAJU PENGERINGAN - Halimursyadah Halimursyadah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
ABSTRACT The objective of this study was to evaluate anatomical changes and oligosaccharide content of recalcitrant seed Avicennia marina at various drying rate i.e. fast, medium and slow drying. Oligosaccharide content was determined, and anatomical embryonic axes was observed at various times during desiccation. The result showed that moisture content of A. marina seed was 60.75-64.67% at shedding. The highest ratio of (raffinose + stachyose) / sucrose was 0.41, indicating that embryonic axes were more tolerant to desiccation than cotyledon. Anatomical observation of embryonic axes showed that there was radicle damage due to medium and slow drying treatment.